In both cases you may well benefit from graphing the functions.
Do you recognize f(x) = (x + 1)^2 - 1 as a quadratic function, whose graph is that of a parabola that opens up? By comparing this to y = a(x-h)^2 + k, we see that a=1, h= -1 and k = -1. The vertex is at (h,k), which here is the point (-1, -1). This is the minimum value of the function. Thus, the range of this function is [-1, infinity).
Now for the function f(x) = 7x - 11: This is a linear function whose graph is (surprise!) a straight line. When x increases, y increases, without limits to either. Similarly, when x decreases, y decreases.
Thus the range includes all real numbers: (-infinity, infinity).
Your Answer should be True
Answer:
![y-2=\displaystyle -\frac{3}{4}(x-1)](https://tex.z-dn.net/?f=y-2%3D%5Cdisplaystyle%20-%5Cfrac%7B3%7D%7B4%7D%28x-1%29)
OR
![y=\displaystyle -\frac{3}{4}x+\frac{11}{4}](https://tex.z-dn.net/?f=y%3D%5Cdisplaystyle%20-%5Cfrac%7B3%7D%7B4%7Dx%2B%5Cfrac%7B11%7D%7B4%7D)
Step-by-step explanation:
Hi there!
Point-slope form:
where <em>m</em> is the slope of the line and
is a given point
Given that the slope is -3/4, we can plug it into
as <em>m</em>:
![y-y_1=\displaystyle -\frac{3}{4}(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3D%5Cdisplaystyle%20-%5Cfrac%7B3%7D%7B4%7D%28x-x_1%29)
We can also plug in the given point (1,2):
![y-2=\displaystyle -\frac{3}{4}(x-1)](https://tex.z-dn.net/?f=y-2%3D%5Cdisplaystyle%20-%5Cfrac%7B3%7D%7B4%7D%28x-1%29)
Slope-intercept form:
where <em>m</em> is the slope and <em>b</em> is the y-intercept (the value of y when the line crosses the y-axis)
To write the equation in slope-intercept form, isolate <em>y</em>:
![y-2=\displaystyle -\frac{3}{4}(x-1)\\\\y=\displaystyle -\frac{3}{4}(x-1)+2\\\\y=\displaystyle -\frac{3}{4}x+\frac{3}{4}+2\\\\y=\displaystyle -\frac{3}{4}x+\frac{11}{4}](https://tex.z-dn.net/?f=y-2%3D%5Cdisplaystyle%20-%5Cfrac%7B3%7D%7B4%7D%28x-1%29%5C%5C%5C%5Cy%3D%5Cdisplaystyle%20-%5Cfrac%7B3%7D%7B4%7D%28x-1%29%2B2%5C%5C%5C%5Cy%3D%5Cdisplaystyle%20-%5Cfrac%7B3%7D%7B4%7Dx%2B%5Cfrac%7B3%7D%7B4%7D%2B2%5C%5C%5C%5Cy%3D%5Cdisplaystyle%20-%5Cfrac%7B3%7D%7B4%7Dx%2B%5Cfrac%7B11%7D%7B4%7D)
I hope this helps!
Answer:
x=750
Step-by-step explanation:
45×100÷6
Answer:
LCM :
6 x 1 = 6
6 x 2 = 12
6 x 3 = 18
6 x 4 = 24
Meanwhile
4 x 1 = 4
4 x 2 = 8
4 x 3 = 12
4 x 4 = 16
4 x 5 = 20
4 x 6 = 24
The LCM of 6 and 4 is 12
HCF:
36 : 1,2,3,4,6,9,12,36
24 : 1,2,3,4,6,8,12,24
HCF of 36 and 24 is 12
So therefore Hussein is correct because both the LCM and HCF is 12